Urbanization alters the relationship between coloration and territorial aggression, but not hormones, in song sparrows. (August 2018) - Beck, Michelle L.; Davies, Scott; Sewall, Kendra B.
Abstract : Melanin-based coloration is associated with aspects of phenotype, including conspecific aggression and hormone concentrations. These relationships could arise as a result of genetic and/or biochemical links between melanin production and other traits. Additionally, anthropogenic change, including urbanization, exposes animals to novel conditions that can alter pigmentation, behaviour or hormones, potentially disrupting relationships between coloration and other traits. We examined relationships among the extent and darkness of melanin spotting on the breast of male song sparrows, Melospiza melodia, territorial behaviour, plasma testosterone and corticosterone concentrations to determine whether coloration was reliably associated with phenotype in this species. We conducted this study in urban and rural populations to determine whether relationships between coloration, behaviour and hormones varied between habitats. Males in urban habitat had more extensive brown spotting than rural males. The relationship between melanin coloration and territoriality differed in urban and rural habitats. In rural sparrows, territoriality was negatively correlated with spotting area, while in urban sparrows territoriality was positively associated with spotting darkness. Regardless of habitat, males with more extensive spotting increased testosterone secretion more in response to gonadotropin-releasing hormone administration and males with darker spotting had greater handling restraint-induced release of corticosterone. This suggests that plumage coloration is associated with underlying physiology, but the relationship between coloration and behaviour may shift between habitats. Highlights: Urban song sparrows have more extensive chest spotting than rural ones. The relationship between coloration and aggression differs between habitats. Melanin coloration is positively related to GnRH-induced testosterone. Melanin coloration is negatively related to restraint-induced corticosterone.